Stem Cell Transplantation Therapy in Systemic Sclerosis: A Systematic Review - Arif Rachman; Prihati Pujowaskito; Arfiyanti Arfiyanti; Arya Duta Dharma; Dinda Puspa; Jafar Elyas; Ilham Syahputro; Nuzuludz Dzikra; Nabil Ramaseno; Ni Made Ayu Widiyasih; Muhammad Zhafran Maulana; Shalya Regita; Ruth Je Deborah Octavia (Perkumpulan Kedokteran Militer, 2025)
Background: Systemic sclerosis (SSc) is a chronic autoimmune disease characterized by systemic inflammation, vascular dysfunction, progressive fibrosis, multiorgan involvement, and impaired quality of life. Autologous hematopoietic stem cell transplantation (HSCT) has been investigated as an option for patients with severe SSc who respond inadequately to conventional immunosuppressive therapy. Methods: A systematic search was conducted in the Cochrane Library and PubMed using terms related to stem cell transplantation, hematopoietic stem cell transplantation, systemic sclerosis, stem cell therapy, immunomodulatory therapy, and cyclophosphamide. Eligible studies were randomized controlled trials involving adults with diffuse or limited SSc, autologous HSCT as the intervention, and cyclophosphamide or other immunomodulatory therapy as the comparator. Study selection, data extraction, and risk-of-bias assessment were performed systematically, and the selection process was documented using a PRISMA flow diagram. Discussion: Three randomized controlled trials involving 250 participants were included. Selective non-myeloablative HSCT improved event-free survival, while selective myeloablative HSCT showed benefits in survival analysis and skin-related outcomes. Quality-of-life improvements were reported with selective HSCT approaches. However, HSCT was associated with a higher risk of serious adverse events than cyclophosphamide. Conclusion: Autologous HSCT may provide clinical benefit in selected patients with severe SSc, but careful risk-benefit assessment, strict patient selection, and long-term monitoring are essential.